Awareness And Utilization of Health Insurance Services by The Families Residing at Urban Field Practice Area of a Medical College in Bangalore - Ramegowda, Chethana; Shivalingaiah, Anwith H (National Journal of Community Medicine, 2015)
Introduction: According to WHO (2012) only 25% of total Indian population is covered by some form of Health Insurance. To achieve Universal health coverage (UHC), World Bank & WHO, have developed a framework which includes financial risk protection, as one of the component. Materials & Methods: A community based cross sectional study was done & a total of 447 households meeting inclusion and exclusion criteria were interviewed. Data regarding sociodemographic profile, awareness regarding health insurance, posession of health insurance was collected. Only beneficiaries of Vajpayee Arogyashree scheme were interviewed regarding awareness & utilisation of same. Results: Mean age of the Head of the Family of study households was 41+ 12years. Most of the households were headed by males [89.7%]. Majority [79%] belonged to Upper lower class of socioeconomic status. Only 10.5 % of the study households were aware regarding health insurance & only 6.7% of the total households were covered under some form of health insurance. Out of these, only 1.6% of the study households were covered under Vajpayee Arogyashree. None of the study households had utilised Vajpayee Arogyashree in the last 1 year. Conclusion: Awareness campaign should be undertaken to increase the awareness regarding government health insurance schemes among its beneficiaries, thereby, reducing the out of pocket expenditures as well financial catastrophes during the illness.